2020
DOI: 10.1007/s12264-020-00587-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice

Abstract: General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
4
4
0
Order By: Relevance
“…No significant difference was recorded between total and soluble cortical glycogen in WT mice (Figure 2(b)), suggesting that most glycogen ($88%) is readily accessible in its soluble form. Of note, and as expected, total cortical and cerebellar glycogen contents in WT mice were respectively one-and two-orders of magnitude lower than that of the glycogen-rich organs skeletal muscle and liver 52 and consistent with several other studies, [53][54][55][56] but lower than the highest reported values 57 (Table S1).…”
Section: Defective Brain Glycophagy In Wdfy3 þ/Lacz Micesupporting
confidence: 92%
“…No significant difference was recorded between total and soluble cortical glycogen in WT mice (Figure 2(b)), suggesting that most glycogen ($88%) is readily accessible in its soluble form. Of note, and as expected, total cortical and cerebellar glycogen contents in WT mice were respectively one-and two-orders of magnitude lower than that of the glycogen-rich organs skeletal muscle and liver 52 and consistent with several other studies, [53][54][55][56] but lower than the highest reported values 57 (Table S1).…”
Section: Defective Brain Glycophagy In Wdfy3 þ/Lacz Micesupporting
confidence: 92%
“…To assess whether depression can be alleviated by enhancing glycogenolysis at the gene level, we used an astrocyte-specific PYGB over-expression (KI-Pygb) mouse model ( Cai et al, 2020 ). As previously reported ( Fan et al, 2020 ), homozygous Pygb H 11/ H 11 mice and WT littermate genotypes were identified by PCR ( Figure 4A ). PYGB and phosphorylated PYGB protein levels were increased in homozygous Pygb H 11/ H 11 mice when compared with WT littermate controls ( Fan et al, 2020 ).…”
Section: Resultssupporting
confidence: 76%
“…As previously reported ( Fan et al, 2020 ), homozygous Pygb H 11/ H 11 mice and WT littermate genotypes were identified by PCR ( Figure 4A ). PYGB and phosphorylated PYGB protein levels were increased in homozygous Pygb H 11/ H 11 mice when compared with WT littermate controls ( Fan et al, 2020 ). Behavioral analyses were performed in the CD1 attack period, according to the timeline shown in Figure 4B .…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Further related to the glucose metabolism, another feature that is peculiar to astroglial cells (although not exclusive) is the glycogen storage, which can be mobilised in the events of increased energy demand and during brain repair [97,221]. The evidence for this is based on the observations that glycogen levels in the brain are increased when neuronal activity is inhibited (e.g., under general anaesthesia) [227]. Moreover, reactive astrocytes in the vicinity of damaged neuropil exhibit the increased accumulation of glycogen [228], which is interesting in view of the upregulation in astroglial GLP-1 receptor expression following ischaemic injury, as mentioned above [218].…”
Section: Effects Of Glp1-ras At the Nvumentioning
confidence: 99%